Optimal social assistance and unemployment insurance in a life-cycle model of family labor supply and savings - Peter Haan; Victoria Prowse (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We empirically analyze the optimal mix and optimal generosity of unemployment insurance and social assistance programs. To do so, we specify a structural life-cycle model of the labor supply, savings, and social assistance claiming decisions of singles and married couples. Partial insurance against wage and employment shocks is provided by social programs, savings, and the labor supplies of all adult household members. We show that the optimal policy mix is dominated by moderately generous social assistance, which guarantees a permanent universal minimum household income, with only a minor role for temporary earnings-related unemployment insurance. The optimal amount of social assistance is heavily influenced by income pooling in married households. This pooling provides partial insurance against negative economic shocks, reducing the optimal generosity of social assistance.
Keywords: J18; J68; H21; I38; 330; Unemployment insurance; Social assistance; Design of benefit programs; Life-cycle labor supply; Family labor supply; Intra-household insurance; Household savings; Employment risk; Added worker effect